PENERAPAN COGNITIVE BEHAVIORAL THERAPY (CBT) DAN PERAN RELIGIUSITAS DALAM MENINGKATKAN POLA PIKIR ADAPTIF ANAK BINAAN LPKA KELAS I TANGERANG YANG BERPERILAKU MENYIMPANG - Nadila, Yulianti Aisah; Warih Handoyo, Alfiiandy; Muhibah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the application of Cognitive Behavioral Therapy (CBT) in individual counseling for a juvenile inmate at LPKA Kelas I Tangerang who engaged in deviant behavior, and to connect the client’s level of religiosity with adaptive mindset changes. The research method used a qualitative case study with three counseling sessions. The results showed changes in the client’s mindset from negative to more adaptive, with awareness to balance religious, social, and daily behavioral values. CBT proved effective in helping the client identify irrational thoughts, transform them into rational ones, and enhance religiosity as a coping mechanism. Parental emotional support was also found to be a crucial factor in preventing deviant behavior.